Nickel nanoparticles, their manufacturing method, paste material and multilayer ceramic capacitor
By controlling stirring power and gas components during the synthesis of nickel nanoparticles, the method achieves uniform particle sizes and high purity, addressing aggregation issues and enhancing performance in applications like MLCC and electromagnetic wave shields.
Patent Information
- Application Number
- JP2021060763
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Existing methods for producing nickel nanoparticles struggle with achieving uniform particle sizes below 100 nm, leading to issues with particle aggregation and poor dispersibility in non-polar solvents, which affects their performance in applications like MLCC and electromagnetic wave shields.
The method involves controlling stirring power and gas components during the synthesis of nickel nanoparticles, resulting in particles with a narrow size distribution and high purity, characterized by an average diameter of 5 to 100 nm and a low coefficient of variation.
This approach enables the production of nickel nanoparticles with excellent thin film formation and filling properties, even in extremely narrow gaps, while maintaining high nickel purity, thus enhancing the performance and reliability of applications such as MLCC and electromagnetic wave shields.
Smart Images

Figure 0007662378000002 
Figure 0007662378000003 
Figure 0007662378000004
Abstract
Description
[Technical field]
[0001] The present invention relates to nickel nanoparticles, a manufacturing method thereof, a paste material, and a multilayer ceramic capacitor. [Background technology]
[0002] MLCC (Multilayer Ceramic Condenser) consists of ceramic dielectric layers and internal electrode layers laminated alternately and integrated together, and is becoming thinner and more multi-layered with the aim of miniaturization and higher capacity. As the films become thinner, the particles used in the dielectrics and electrodes also become finer, which has resulted in the problem of particle aggregation becoming evident, requiring advanced dispersion technology and particle shape control technology.
[0003] In terms of particle shape, when the paste is stretched to form a thin film, if there are large particles with a wide particle size distribution, problems such as liquid cutting will occur starting from the large particles, making it impossible to apply a uniform thickness. In order to apply uniform tension to the entire paste, it is necessary for the large particles to be of uniform diameter and to be arranged in a balanced manner in a certain amount.
[0004] In addition, in applications such as forming wiring for electromagnetic shielding and touch panels, the filling of grooves in nanoimprinted substrates with metal particles is being considered to prevent bleeding and spreading. It is known that, even when densely filling narrow grooves, uniform particle size maintains uniform tension throughout the paste, making it easier to achieve dense filling.
[0005] As a method for producing uniform particles, there is a method for producing nickel particles (Patent Document 1) in which nickel hydroxide particles obtained by reacting nickel salt with an alkali metal hydroxide in water are reduced with hydrazine. The particles produced by this method are nickel particles with an average particle size of 0.44 to 0.51 μm, and have a narrow particle size distribution in which the number of particles having a particle size of 1.2 times or more of the average particle size observed by scanning electron microscope (SEM) is 5% or less of the total number of particles, and the number of particles having a particle size of 0.8 times or less of the average particle size is 5% or less of the total number of particles. Since the reaction is carried out in an aqueous solution, the hydroxide cannot be completely removed, and sufficient dispersibility cannot be obtained when applied to a particle size of 100 nm or less, or when applied to a non-polar solvent that is preferably used for the above-mentioned applications. Therefore, there is a problem that particles aggregate with each other. In addition, it is difficult to synthesize particles with a uniform particle size of 100 nm or less.
[0006] As a method for producing uniform particles of 100 nm or less, it has been reported that uniform particles with a coefficient of variation CV of 0.2 or less can be obtained by using seed particles of 10 nm to 50 nm obtained by adding copper formate to a salt containing nickel carboxylate and reducing it with an amine (Patent Document 2), but copper is used for the seed particles. In other examples of Patent Document 2, copper formate is not used, but silver nitrate, palladium acetate, chloroplatinic acid hexahydrate, or chloroauric acid tetrahydrate is used, and all of them use a different metal other than nickel in combination. From the viewpoints of electrical properties and cost, nickel particles with nickel purity as high as possible are required. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 3280372 [Patent Document 2] WO2016 / 052067 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide high-purity nickel nanoparticles of 10 to 100 nm that are excellent in thin-film formability and filling ability into extremely narrow gaps. [Means for solving the problem]
[0009] As a result of extensive research, the inventors discovered that by controlling the stirring power and the gas components generated during the synthesis of nickel nanoparticles, it is possible to produce nickel nanoparticles that have a uniform particle size, even when observed with a high-resolution SEM, and thus completed the present invention.
[0010] That is, the present invention relates to nickel nanoparticles having an average particle diameter of 5 to 100 nm and containing 99.5 parts by weight or more of nickel component contained in 100 parts by weight of metal component, characterized in that, in a total of 400 nickel nanoparticles photographed with a scanning electron microscope (SEM) having a secondary electron resolution of 1.0 nm or less at an accelerating voltage of 15 kV, the combined number of particles having a particle diameter of 1 / 2 or less and particles having a particle diameter of 3 / 2 or more of the average particle diameter accounts for 5% or less.
[0011] The nickel nanoparticles of the present invention preferably contain 0.00003 to 0.5 parts by weight of lithium.
[0012] The method for producing nickel nanoparticles of the present invention is a method for producing nickel nanoparticles by heating a nickel complexation reaction liquid obtained by reacting a nickel salt with a reducing agent, thereby reducing nickel ions in the nickel complexation reaction liquid. The method for producing nickel nanoparticles of the present invention is characterized in that, while blowing in nitrogen at 0.1 to 5 L / min per 100 g of nickel complexation reaction solution, the power of the stirrer is adjusted to within the range of 0.025 to 0.1 kW, and then the solution is heated to 190 to 240°C to produce nickel nanoparticles.
[0013] Furthermore, in the method for producing nickel nanoparticles of the present invention, the nitrogen flow rate may be changed in the temperature range of 190 to 215° C. In this case, the nitrogen flow rate may be adjusted to 2 to 4 L / min at temperatures below 200° C., and 0.1 to 1.8 L / min at temperatures of 200° C. or higher.
[0014] The paste material of the present invention is characterized by being obtained by mixing the nickel nanoparticles and a resin.
[0015] The multilayer ceramic capacitor of the present invention is characterized in that the nickel nanoparticles are used as an electrode material. Effect of the Invention
[0016] The nickel nanoparticles of the present invention have a total particle size of 5% or less, including particles with a diameter of 1 / 2 or less of the average particle size and particles with a diameter of 3 / 2 or more of the average particle size, even when observed with a high-resolution SEM with a secondary electron resolution of 1.0 nm or less at an accelerating voltage of 15 kV. This means that the tension acting inside the paste during thin film formation is uniform, facilitating the formation of a uniform ultra-thin film, and the nanoparticles can be suitably used in applications requiring multilayer thin film stacking, such as MLCCs (multilayer ceramic condensers). Furthermore, the paste material using the nickel nanoparticles of the present invention can be widely used for applications such as electromagnetic shielding and touch panels, as a material for filling grooves formed by printing with paste to prevent bleeding and spreading of wiring. [Brief description of the drawings]
[0017] [Figure 1] 1 is a scanning electron microscope (SEM) image (200,000x) of the particles prepared in Example 1. [Diagram 2] 1 is an SEM image (200,000 times) of the particles prepared in Comparative Example 1. [Diagram 3] 1 is an SEM image (200,000 times) of particles prepared in Comparative Example 2. [Figure 4] 1 is an SEM image (100,000x) of the particles prepared in Example 2. [Diagram 5] 1 is an SEM image (200,000 times) of particles prepared in Comparative Example 3. [Figure 6] 1 is an SEM image (200,000x) of the particles prepared in Example 3. [Figure 7] 1 is an SEM image (200,000 times) of particles prepared in Comparative Example 4. [Figure 8] 1 is an SEM image (200,000x) of the particles prepared in Example 4. [Figure 9] 1 is an SEM image (200,000 times) of particles prepared in Comparative Example 5. [Figure 10] 1 is an SEM image (200,000x) of the particles prepared in Example 5. [Figure 11] 1 is an SEM image (50,000x) of particles prepared in Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An embodiment of the present invention will be described below. The nickel nanoparticles of the present invention are nickel nanoparticles having an average particle diameter of 5 to 100 nm and containing 99.5 parts by weight or more of nickel component contained in 100 parts by weight of metal component, and in a total of 400 nickel nanoparticles photographed with an SEM having a secondary electron resolution of 1.0 nm or less at an acceleration voltage of 15 kV, the ratio of the total number of particles having a particle diameter of 1 / 2 or less (hereinafter sometimes referred to as "relatively small particles") and particles having a particle diameter of 3 / 2 or more (hereinafter sometimes referred to as "relatively large particles") to the average particle diameter is 5% or less. In this way, since the ratio of the total number of relatively small particles and relatively large particles to the total number of particles is 5% or less, the presence ratio of particles that deviate greatly from the average particle diameter in the particle size distribution is small, and the particle size distribution is sharp, so that the thin film forming property and filling into extremely narrow gaps are excellent.
[0019] The nickel nanoparticles of the prior art are prone to produce relatively small particles, and in applications where ceramic fillers are added to prevent shrinkage during sintering, such as in MLCCs, fine particles are used to fill the gaps between the nickel nanoparticles, so if the ratio of relatively small particles is high, the optimal particle size balance is lost and the viscosity characteristics also change, causing problems in thin film formation and sintering. In addition, if particles larger than twice the average particle size are present, there is a concern that they may penetrate the insulating layer and become conductive when forming multiple layers of thin films such as electrodes, so it is preferable to have a small ratio of relatively large particles. Therefore, it is preferable that the ratio of relatively small particles and relatively large particles to the entire particles is 3% or less, and it is good that the combined ratio of relatively small particles and relatively large particles is 5% or less.
[0020] The nickel nanoparticles of the present invention preferably have a CV value (standard deviation of particle diameters of 400 nickel nanoparticles divided by the average particle diameter) of 0.25 or less, more preferably 0.20 or less, when photographed with an SEM having a secondary electron resolution of 1.0 nm or less at an accelerating voltage of 15 kV.
[0021] The nickel nanoparticles of the present invention have an average particle size of 5 to 100 nm, but the lower limit is preferably 10 nm or more, more preferably 15 nm or more, because the nucleophilic reagent added is expensive and the nickel nanoparticles of the prior art (the content of small-diameter nickel nanoparticles is high). On the other hand, the larger the particle size, the smaller the amount of nucleating agent added, and the lower the accuracy of the particle size, so the upper limit is preferably 90 nm or less, more preferably 80 nm or less.
[0022] The nickel nanoparticles of the present invention contain 99.5 parts by weight or more of nickel component per 100 parts by weight of the metal component. However, 99.8 parts by weight or more is preferable, and 99.95 parts by weight or more is more preferable, because this results in good electrical properties such as electrical conductivity and migration.
[0023] The nickel nanoparticles of the present invention preferably contain 0.00003 to 0.5 parts by weight of lithium because the particle size can be easily controlled. A more preferred lower limit is 0.00005 parts by weight. On the other hand, a more preferred upper limit is 0.2 parts by weight.
[0024] The nickel nanoparticles of the present invention may be core-shell type particles in which the nickel nanoparticles are the core and another metal is the shell. In this case, the nickel nanoparticles of the present invention correspond to the core part of the core-shell type particles. In other words, although the weight part of lithium or the content of alkali metal or alkaline earth metal by ICP mass spectrometry is specified in this specification, they specify the core part of the core-shell type particles.
[0025] The other metal is preferably iron, cobalt, copper, palladium, platinum, gold or tungsten.The average particle size of the core-shell particles is preferably 10 to 105 nm.
[0026] Next, a method for producing nickel nanoparticles according to the present invention will be illustrated. The method for producing nickel nanoparticles according to the present embodiment includes the following steps A and B: A) a step of mixing a nickel salt and a reducing agent to obtain a nickel complexation reaction solution; B) heating the nickel complexation reaction solution to reduce nickel ions in the nickel complexation reaction solution to obtain a slurry of nickel nanoparticles; In the method for producing metal particles according to the present embodiment, the power of the stirrer is adjusted to within a range of 0.025 to 0.1 kW while blowing nitrogen at 0.1 to 5 L / min into 100 g of the nickel complexation reaction solution, and then the solution is heated to 190 to 240° C. to generate nickel nanoparticles. An organometallic compound may be added at any timing between step A and when the metal complexation reaction solution is heated in step B.
[0027] [Process A] Step A is a step of mixing a nickel salt and a reducing agent to obtain a nickel complexation reaction solution.
[0028] <Nickel salt> Examples of nickel salts include known nickel salts. For example, organic acid nickel salts such as nickel carboxylates, and inorganic nickel salts such as nickel chloride, nickel sulfate, nickel nitrate, and nickel carbonate are included. Among these, metal carboxylates having 1 to 12 carbon atoms excluding the COOH group are preferred, which are easy to control the particle size and particle size distribution of nickel nanoparticles. Among these, nickel acetate is more preferred.
[0029] The reducing agent used in the present embodiment is not particularly limited as long as it can form a complex with nickel, but for example, primary amines are preferably used. Primary amines are preferred because they can form a complex with nickel and can effectively exert reducing ability on the nickel complex. On the other hand, secondary amines have a large steric hindrance and may inhibit good formation of the nickel complex, and tertiary amines do not have the ability to reduce nickel, so neither can be used alone, but when using primary amines, they can be used in combination within a range that does not interfere with the shape of the nickel nanoparticles to be generated.
[0030] The reducing agent may be a solid or liquid at room temperature. Here, room temperature refers to 20°C ± 15°C. A primary amine that is liquid at room temperature also functions as an organic solvent when forming a nickel complex. There is no problem with a primary amine that is solid at room temperature, as long as it becomes liquid when heated to 100°C or higher or can be dissolved using an organic solvent.
[0031] The primary amine may be an aromatic primary amine, but an aliphatic primary amine is preferred from the viewpoint of ease of nickel complex formation in the reaction solution. The aliphatic primary amine can control the dispersibility of the nickel nanoparticles produced by, for example, adjusting the length of its carbon chain, and is advantageous in applications requiring dispersibility. From the viewpoint of controlling the aggregation of nickel nanoparticles, it is preferred to select and use an aliphatic primary amine having a carbon number of about 6 to 20. Examples of such amines include octylamine, trioctylamine, dioctylamine, hexadecylamine, dodecylamine, tetradecylamine, stearylamine, oleylamine, myristylamine, and laurylamine. Oleylamine and dodecylamine are particularly preferred because they exist in a liquid state under the temperature conditions in the nickel nanoparticle production process, and therefore the reaction can proceed efficiently in a uniform solution. Oleylamine is the most preferred.
[0032] Since the primary amine functions as a surface modifier during the production of nickel nanoparticles, secondary aggregation can be suppressed even after the removal of the primary amine. In addition, the primary amine is preferably liquid at room temperature from the viewpoint of ease of processing operation in the washing step for separating the solid component of the produced nickel nanoparticles from the solvent or unreacted primary amine after the reduction reaction in step B. Furthermore, the primary amine is preferably one having a boiling point higher than the reduction temperature from the viewpoint of ease of reaction control when reducing the nickel complex to obtain nickel nanoparticles. The amount of the primary amine is preferably used at a ratio of 2×1 times the valence of nickel or more per mol of nickel, more preferably 2×1.1 times the valence or more, and even more preferably 2×2 times the valence or more. If the amount of the primary amine is less than 2×1 times the valence of nickel, it becomes difficult to control the particle size of the obtained nickel nanoparticles, and the particle size tends to vary. In addition, there is no particular upper limit to the amount of the primary amine, but from the viewpoint of productivity, it is preferable to use an amount of 2×10 times the valence of nickel or less.
[0033] The conditions for forming the nickel complexing reaction solution in step A, that is, the conditions for mixing the nickel salt and the reducing agent, will be described using an example in which nickel carboxylate and a primary amine are used as the reducing agent. In this case, the complexing reaction can proceed even at room temperature, but in order to perform a sufficient and more efficient complexing reaction, it is preferable to heat the reaction to a temperature in the range of, for example, 100°C to 165°C. The heating temperature is preferably a temperature exceeding 100°C, more preferably a temperature of 105°C or higher, so that the ligand substitution reaction between the coordinated water coordinated to the nickel carboxylate and the primary amine is efficiently performed, the water molecule as the complex ligand can be dissociated, and the water can be removed from the system, so that the complex with the amine can be efficiently formed. The heating time can be appropriately determined depending on the heating temperature and the content of each raw material. There is no particular upper limit to the heating time, but unnecessarily long heat treatment is wasteful from the viewpoint of saving energy consumption and process time.
[0034] The heating method in step A is not particularly limited, and may be, for example, heating with a heat medium such as oil, or heating by microwave irradiation or ultrasonic irradiation.
[0035] In step A, an organic solvent other than the primary amine may be added to allow the reaction in the homogeneous solution to proceed more efficiently. When using an organic solvent, the organic solvent may be mixed simultaneously with the nickel salt and the reducing agent, but it is more preferable to mix the nickel salt and the reducing agent first to form a complex and then add the organic solvent, since the reducing agent is efficiently coordinated to the nickel atom. The organic solvent that can be used is not particularly limited as long as it does not inhibit the complex formation between the nickel salt and the reducing agent and does not oxidize the generated nickel, and for example, a saturated or unsaturated hydrocarbon-based organic solvent having 7 to 30 carbon atoms can be used. In addition, from the viewpoint of being able to use it even under heated conditions, it is preferable to select an organic solvent having a boiling point of 170°C or higher. A specific example of such an organic solvent is paraffin oil.
[0036] [Process B] In step B, an inert gas is blown into the nickel complexation reaction solution obtained by the complexation reaction at a predetermined flow rate, and the power is adjusted according to the liquid volume and the desired particle size, and the solution is heated while being stirred, and nickel in the complexation reaction solution is reduced to obtain a slurry of nickel nanoparticles. Specifically, while blowing in nitrogen at 0.1 to 5 L / min per 100 g of nickel complexation reaction solution, the power of the stirrer is adjusted to within the range of 0.025 to 0.1 kW, and then the solution is heated to 190 to 240°C to generate nickel nanoparticles.
[0037] The heating temperature in step B varies depending on the particle size and particle size distribution of the nickel nanoparticles obtained, but it is preferable to maintain the temperature at which an endothermic reaction occurs. If the temperature is sufficiently high beyond the reaction temperature, the catalytic action of the generated nickel decomposes the hydrocarbons, and carbon precipitates and covers the surface of the nickel nanoparticles, suppressing the generation of nickel ions on the nickel surface. Therefore, when the nickel nanoparticles are used as a paste material, the bonding between the nickel nanoparticles or between the nickel nanoparticles and other particles tends to decrease.
[0038] Here, the inert gas means a chemically stable gas that does not react with other substances used in the synthesis reaction of nickel nanoparticles in step B. Examples include nitrogen and argon. Nitrogen is preferable because it is available at low cost.
[0039] The flow rate of nitrogen, an example of an inert gas, is preferably adjusted to a flow rate according to the gas generated during the reaction, and the range of the flow rate can be appropriately selected since it varies depending on the desired particle size and synthesis amount. Preferably, it is 0.1 to 5 L / min for 100 g of nickel complexing reaction solution. More specifically, when synthesizing particles with a particle size of 15 nm, it is preferably 2 to 4 L / min for 750 g of nickel complexing reaction solution, more preferably 2.8 to 3.2 L / min. In addition, when synthesizing particles with a particle size of more than 30 nm, for example, particles with a particle size of 40 nm, it is preferable to set the nitrogen flow rate to 2 to 4 L / min up to 200 ° C., where the core particles are generated, for 750 g of nickel complexing reaction solution, and the target particles can be obtained by adjusting the nitrogen flow rate to 0.1 to 1.8 L / min at 200 ° C. or higher.
[0040] There is no particular restriction on the purity of the nitrogen, but if there is a lot of moisture, the complex may absorb moisture and affect the reaction, so it is preferable to use nitrogen with a purity of 99.9% or more with a low moisture content. In addition, blowing in nitrogen gas means that the reaction liquid is directly contacted with nitrogen gas at a certain pressure or more, rather than simply being in a nitrogen atmosphere or under nitrogen flow (so-called "nitrogen flow"). The method of blowing in nitrogen gas may be to flow it down toward the reaction liquid surface, or to spray it toward the reaction liquid surface with a known nozzle, or to directly inject nitrogen gas into the reaction liquid. By "blowing in", the gas generated by the reaction (reaction product gas) can be efficiently expelled. It is desirable to adjust the blowing method, flow rate, pressure, etc. according to the desired particle size. If the reaction product gas is not sufficiently removed, nucleation is hindered, and nuclei are generated in stages, resulting in particles with a broad particle size, which is not preferable. In addition, if the reaction product gas is removed too efficiently, new nuclei are generated during the growth reaction after nucleation, and broad particle sizes tend to be generated.
[0041] The power for stirring the reaction solution can be appropriately selected depending on the shape of the stirring blade, etc., but it is preferable to synthesize with a power according to the amount of liquid. For 100 g of nickel complexing reaction solution, the preferred lower limit of the power is preferably 0.02 kW or more to prevent the generation of coarse particles due to the association of particles, and more preferably 0.025 kW or more. In addition, for 100 g of nickel complexing reaction solution, the upper limit of the power is preferably 0.1 kW or less, and more preferably 0.07 kW or less, because there is a risk of quality problems such as the formation of coarse particles due to contamination caused by splashing due to the liquid being violent. In addition, since the gas discharge property changes, it can also cause the generation of new nuclei during the growth reaction, so it is preferable to adjust the power value appropriately.
[0042] The heating time is not particularly limited, but it is preferable to measure the nickel concentration of the reaction solution using, for example, a nickel concentration meter Ni-5Z manufactured by Kasahara Chemical Industry Co., Ltd., and heat until nickel is no longer detected. If the heating time is shorter than this, it is difficult to obtain particles of the desired particle size, and furthermore, the dispersibility is likely to decrease, which is not preferable. In addition, there is no particular upper limit on the heating time because the heating time varies depending on the particle size, but heating for a long time after the reaction is completed is not preferable because carbon precipitates on the nickel surface, and the temperature required for sintering becomes high in applications that do not tolerate impurities, such as applications that require low-temperature sintering. In addition, the amount of gas generated during sintering increases, which is not preferable because the shape of the sintered body is likely to be damaged.
[0043] The production process in step B uses a batch method or a continuous reactor for heating a stainless steel vessel, and examples of the heating means include a heating method using a heat medium such as oil temperature control, electricity, microwaves, and ultrasonic waves. From the viewpoint of production cost, a heating method using a heat medium such as oil temperature control and electricity is preferably used. Heating by microwave irradiation or ultrasonic irradiation may also be used.
[0044] In step B, in order to improve the dispersibility of the nickel nanoparticles or to impart functions such as rust inhibitors to prevent oxidation, dispersants or additives for imparting functions can be added within a range that does not interfere with bonding.
[0045] [Addition of organometallic compounds] The organometallic compound used in this embodiment is not particularly limited as long as it has the same properties (nucleophilicity) as the nucleophilic reagent and acts on the metal complex. From the viewpoints of ease of control of the particle size and particle size distribution of the nickel nanoparticles, safety, simplicity, and productivity, preferred organometallic compounds include alkali metal-based organometallic compounds in which an organic group such as an alkyl group or an alkoxy group is coordinated to an alkali metal, and alkaline earth metal-based organometallic compounds in which the organic group is coordinated to an alkaline earth metal. Hereinafter, the alkali metal-based organic compounds and the alkaline earth metal-based organic compounds are collectively referred to as "the present organometallic compounds". The present organometallic compounds may be organometallic halides containing halides such as chlorine, bromine, and iodine. In this case, they are also referred to as alkali metal-based organometallic halides and alkaline earth metal-based organometallic halides, respectively. An alkali metal-based organometallic halide is one form of an alkali metal-based organometallic compound, and an alkaline earth metal-based organometallic halide is one form of an alkaline earth metal-based organometallic compound.
[0046] Examples of the alkali metal constituting the alkali metal-based organometallic compound include lithium, sodium, potassium, rubidium, and cesium, and organolithium compounds containing highly reactive lithium are preferably used. In addition, examples of the alkaline earth metal constituting the alkaline earth metal-based organometallic compound include beryllium, magnesium, calcium, strontium, and barium, and organomagnesium halides containing magnesium, which has good reactivity, are preferably used. Note that, since alkylaluminum, in which an alkyl group is coordinated to aluminum, is highly flammable, an alkali metal-based organometallic compound is more preferably used from the viewpoints of safety and simplicity.
[0047] The organometallic compound is preferably used as a diluted solution diluted with an organic solvent such as tetrahydrofuran, hexane, toluene, cyclohexane, butyl ether, dibutyl ether, etc., and from the viewpoint of affinity with the nickel complexation reaction solution, a toluene or dibutyl ether solution is particularly preferable. There is no limit to the concentration of the diluted solution, but when a small amount affects the particle size, a low concentration is preferable because it is easier to control.
[0048] As the alkali metal-based organometallic compound, inexpensive and versatile n-butyllithium or phenyllithium is preferably used, and a dibutyl ether solution of phenyllithium is particularly preferable from the viewpoints of safety and simplicity.
[0049] The amount of the organometallic compound to be added is not particularly limited, since it is sufficient to select the amount according to the target particle size. Specifically, the amount of the organometallic compound to be added is preferably within a range of 0.001 to 30, more preferably within a range of 0.003 to 10, per 100 g of nickel complex.
[0050] The organometallic compound may be added at any timing between step A and heating the complexing reaction solution in step B. For example, the organometallic compound may be added after mixing the nickel salt and the reducing agent in step A and removing excess water, or after preparing the complexing reaction solution. In addition, the organometallic compound is deactivated by water and loses its effect, making it difficult to control the particle size distribution, so it is preferable to add it just before heating the complexing reaction solution in step B. By adding the organometallic compound, the particle size of the nickel nanoparticles can be significantly reduced. Although the mechanism of action is not yet clear, it is presumed that the organometallic compound having nucleophilicity acts on the nickel complex and promotes the generation of nickel nuclei.
[0051] The nickel nanoparticles of the present invention can be mixed with a known resin to form a paste material. For example, the resin can be used as an organic binder. The organic binder has the role of suppressing the precipitation or aggregation of the nickel nanoparticles in the paste material and maintaining the dispersibility. In addition, the nickel nanoparticles are connected to each other or to other particles to form a wide-ranging network structure, which contributes to the formation of a bonding layer with high bonding strength. The known resin can be used without any particular limitation as long as it is a binder that can be dissolved in an organic solvent, and examples of the known resin include thermosetting resins such as phenol resins, epoxy resins, unsaturated polyester resins, urea resins, and melamine resins, and thermoplastic resins such as polyethylene resins, acrylic resins, methacrylic resins, nylon resins, acetal resins, and polyvinyl acetal resins. Among these, polyvinyl acetal resins are preferred, and in particular, polyvinyl acetal resins having an acetal group unit, an acetyl group unit, and a hydroxyl group unit in the molecule are more preferred.
[0052] The paste material may contain other particles as an optional component. That is, the paste material may contain the nickel nanoparticles and other particles. Here, the material and shape of the other particles are not limited, but examples of the metal elements include base metals such as tin, titanium, cobalt, copper, chromium, manganese, iron, zirconium, tungsten, molybdenum, and vanadium, which have excellent thermal conductivity as a sintering material, and precious metals such as gold, silver, platinum, palladium, iridium, osmium, ruthenium, rhodium, and rhenium. These may be contained alone or in combination of two or more. More preferably, they are cobalt, silver, copper, and solder, which have excellent thermal conductivity and sintering properties.
[0053] Since the paste material contains the nickel nanoparticles of the present invention as an essential component, the tension acting inside the paste during the formation of the thin film acts uniformly, making it easy to form a uniform ultra-thin film. In addition, the paste has excellent filling properties in grooves and linearity of wiring. Therefore, it can be suitably used for applications requiring multi-layer thin film lamination, such as MLCC. In addition, the paste can be widely used in applications such as electromagnetic shielding and touch panels as a material for filling grooves formed by printing with paste in order to prevent bleeding and spreading of wiring.
[0054] The following is an example of the use of the paste material for MLCC, particularly when nickel nanoparticles are used as an electrode material for MLCC.
[0055] [Internal electrodes for multilayer ceramic capacitors] The internal electrodes of the multilayer ceramic capacitor of this embodiment (hereinafter also simply referred to as "internal electrodes") are manufactured by making the nickel nanoparticles of this embodiment into a paste and printing it on a ceramic substrate. When forming the paste, a known viscosity modifier such as an organic vehicle or an aqueous vehicle may be mixed in. By mixing the viscosity modifier, appropriate fluidity and volatility are imparted to the paste, and smooth internal electrodes can be formed on the ceramic substrate. The organic vehicle is, for example, a resin dissolved in an organic solvent. The resin used in the organic vehicle is not particularly limited, and may be appropriately selected from various ordinary resins such as ethyl cellulose and polyvinyl butyral. The organic solvent used is also not particularly limited, and may be appropriately selected from various organic solvents such as terpineol, butyl carbitol, acetone, and toluene depending on the method used, such as a printing method or a sheet method. Examples of the aqueous vehicle include polyvinyl alcohol, cellulose, and water-soluble acrylic resin. The ceramic substrate may be a known one, such as a perovskite-based dielectric material having barium titanate, a portion of the titanium therein substituted with zircon, or a portion of the barium therein substituted with strontium, calcium, or the like. The printing method for the internal electrodes is not particularly limited as long as it is a method capable of forming a uniform layer, and examples thereof include screen printing, gravure printing, vapor deposition, sputtering, and inkjet printing.
[0056] [Multilayer ceramic capacitors] The multilayer ceramic capacitor of the present embodiment is manufactured by stacking the internal electrodes and ceramic dielectrics alternately in layers, pressing them together, and sintering them to integrate them. The ceramic derivative is a known one, such as barium titanate. This is made into a paste, and a layer is formed on the internal electrodes. When making the paste, a known viscosity modifier such as an organic vehicle or a water-based vehicle may be mixed. By mixing the viscosity modifier, the paste is given appropriate fluidity and volatility, and a smooth internal electrode can be formed on the ceramic substrate. The organic vehicle is, for example, a resin dissolved in an organic solvent. The resin used in the organic vehicle is not particularly limited, and may be appropriately selected from various ordinary resins such as ethyl cellulose and polyvinyl butyral. The organic solvent used is also not particularly limited, and may be appropriately selected from various organic solvents such as terpineol, butyl carbitol, acetone, and toluene depending on the method used, such as a printing method or a sheet method. Examples of the aqueous vehicle include polyvinyl alcohol, cellulose, and water-soluble acrylic resin. The method for printing the ceramic dielectric material is not particularly limited as long as it is a method capable of forming a uniform layer, and examples thereof include screen printing, gravure printing, vapor deposition, sputtering, and inkjet printing. The number and thickness of the internal electrodes and ceramic dielectric layers are not limited, but may be, for example, several to 1000 layers, with each layer having a thickness of 0.1 μm to 2 μm. Next, the multi-layer structure of the internal electrodes and ceramic dielectric thus obtained is pressed together to form an integral body, cut to a predetermined size (chip size), and fired to form a chip. The firing temperature is, for example, 1000° C. to 1300° C. After firing, a metal paste is applied to both end faces of the chip, heat-treated, and the surface is plated to form external electrodes.
[0057] The multilayer ceramic capacitor according to the embodiment of the present invention thus manufactured is mounted on a printed circuit board by soldering or the like and used in various electronic devices. Such electronic devices use the nickel nanoparticles of the present invention, and therefore can be made small and have high capacity, are excellent in reliability and life, and can improve the high-temperature load life of electronic components. EXAMPLES
[0058] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, unless otherwise specified, measurements and evaluations were performed according to the following methods.
[0059] [Measurement of particle size distribution, average particle size and CV value] The particle size distribution, average particle size and CV value were measured by the following methods. A photograph of the sample was taken using an SEM (scanning electron microscope, Hitachi High-Tech Corporation's Regulus 8100, secondary electron resolution 0.8 nm at an accelerating voltage of 15 kV), and 400 particles in which the entire particle was captured were extracted sequentially from the left side of the photograph using particle size distribution analysis software (Mountec's MacView). The circular diameter (Heywood diameter) equivalent to the selected area was taken as the individual particle diameter, and the mathematical mean diameter and standard deviation were calculated. For all 400 extracted nickel nanoparticles, the ratio (%) of particles with a particle diameter of 1 / 2 or less (≦1 / 2 particle diameter) to particles with a particle diameter of 3 / 2 or more (≧3 / 2 particle diameter) was calculated. The CV value (coefficient of variation) was calculated by dividing the standard deviation by the mathematical mean diameter. A smaller CV value indicates a more uniform particle diameter.
[0060] [Organometallic compound] Organometallic compound (1): Fujifilm Wako Pure Chemical Industries, Ltd., phenyllithium in approximately 19% dibutyl ether solution (approximately 1.9 mol / L)
[0061] [Oleylamine] Nissan Amine OB manufactured by NOF Corporation
[0062] (Synthesis Example 1) 600 g of oleylamine was placed in a 2 L four-neck flask, 246.8 g of nickel acetate tetrahydrate was added, and the mixture was reacted at 140° C. for 3 hours under a nitrogen flow of 2 L / min to obtain 775 g of nickel complexation reaction solution A.
[0063] (Synthesis Example 2) 200 g of oleylamine was placed in a 2 L four-neck flask, 82.3 g of nickel acetate tetrahydrate was added, and the mixture was reacted at 140° C. for 3 hours under a nitrogen flow of 2 L / min to obtain 258 g of nickel complexation reaction solution B.
[0064] Example 1 6 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 781 g, and while directly injecting nitrogen gas into the reaction solution at 3 L / min, the power was adjusted to 0.034 kW, the temperature was raised with a mantle heater, and the reaction was carried out at 210 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in Figure 1 and Table 1, particles showing a sharp particle size distribution with an average particle diameter of 14.9 nm and a CV value of 0.12 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.85 parts by weight.
[0065] Example 2 0.15 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 775.15 g, and while directly injecting nitrogen gas into the reaction solution at 1 L / min, the power was adjusted to 0.033 kW, the temperature was raised with a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 4 and Table 1, particles showing a sharp particle size distribution with an average particle diameter of 27.9 nm and a CV value of 0.14 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0066] Example 3 0.17 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1, making the total amount 775.17 g, and while directly injecting nitrogen gas into the reaction solution at 3 L / min, the power was adjusted to 0.048 kW, and the temperature was raised with a mantle heater. When the temperature reached 200 ° C, the amount of nitrogen was switched to 0.5 L / min, and the reaction was carried out at 230 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 6 and Table 1, particles showing a sharp particle size distribution with an average particle diameter of 38.2 nm and a CV value of 0.17 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0067] Example 4 13.2 g of the nickel nanoparticle slurry obtained in Example 1 was added to 258 g of the nickel complexation reaction solution B obtained in Synthesis Example 2, making the total amount 271.2 g, and while directly injecting nitrogen gas into the reaction solution at 0.5 L / min, the power was adjusted to 0.029 kW, the temperature was raised with a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain a nickel nanoparticle slurry. As shown in FIG. 8 and Table 1, particles showing a sharp particle size distribution with an average particle diameter of 41.0 nm and a CV value of 0.19 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0068] Example 5 5 g of the nickel nanoparticle slurry obtained in Example 1 was added to 258 g of the nickel complexation reaction solution B obtained in Synthesis Example 2 to make a total of 263 g, and while directly injecting nitrogen gas into the reaction solution at 1 L / min, the power was adjusted to 0.033 kW, the temperature was raised with a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain a nickel nanoparticle slurry. As shown in FIG. 10 and Table 1, particles showing a sharp particle size distribution with an average particle diameter of 49.8 nm and a CV value of 0.18 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0069] Comparative Example 1 6 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 781 g, and while flowing nitrogen gas at 2 L / min, the power was adjusted to 0.033 kW, the temperature was raised by a mantle heater, and the reaction was carried out at 210 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 2 and Table 1, particles showing a broad particle size distribution with an average particle diameter of 18.4 nm and a CV value of 0.29 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.85 parts by weight.
[0070] Comparative Example 2 6 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 781 g, and while flowing nitrogen gas at 4 L / min, the power was adjusted to 0.033 kW, the temperature was raised by a mantle heater, and the reaction was carried out at 210 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 3 and Table 1, particles showing a broad particle size distribution with an average particle diameter of 20.4 nm and a CV value of 0.24 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.85 parts by weight.
[0071] Comparative Example 3 0.2 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 775.2 g, and while flowing nitrogen gas at 3 L / min, the power was adjusted to 0.033 kW, the temperature was raised by a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 5 and Table 1, particles showing a broad particle size distribution with an average particle diameter of 27.8 nm and a CV value of 0.27 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0072] Comparative Example 4 0.2 g of organometallic compound (1) was added to 775 g of nickel complexation reaction solution A obtained in Synthesis Example 1 to make a total of 775.2 g, and while flowing nitrogen gas at 3 L / min, the power was adjusted to 0.048 kW, the temperature was raised by a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain nickel nanoparticle slurry. As shown in FIG. 7 and Table 1, particles showing a broad particle size distribution including fine particles of 10 to 20 nm with an average particle diameter of 36.6 nm and a CV value of 0.36 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0073] Comparative Example 5 13.2 g of the nickel nanoparticle slurry obtained in Example 1 was added to 258 g of the nickel complexation reaction solution B obtained in Synthesis Example 2, making the total amount 271.2 g. While flowing nitrogen gas at 3 L / min, the power was adjusted to 0.029 kW, the temperature was raised by a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain a nickel nanoparticle slurry. As shown in FIG. 9 and Table 1, particles showing a broad particle size distribution with an average particle diameter of 36.5 nm and a CV value of 0.55 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0074] Comparative Example 6 4.0 g of the nickel nanoparticle slurry obtained in Example 1 was added to 258 g of the nickel complexation reaction solution B obtained in Synthesis Example 2 to make a total of 262 g, and the power was adjusted to 0.018 kW while flowing nitrogen gas at 1 L / min, and the temperature was raised by a mantle heater, and the reaction was carried out at 230 ° C for 10 minutes to obtain a nickel nanoparticle slurry. As shown in FIG. 11 and Table 1, particles showing a broad particle size distribution with an average particle diameter of 49.3 nm and a CV value of 0.31 were obtained. In addition, the nickel component contained in 100 parts by weight of the metal component was 99.99 parts by weight.
[0075] [Table 1]
[0076] As shown in Table 1, the nickel nanoparticles of the present invention in Examples 1 to 5 were photographed with a high-resolution SEM with a secondary electron resolution of 1.0 nm or less at an acceleration voltage of 15 kV, and the total number of particles with a particle diameter of 1 / 2 or less and particles with a particle diameter of 3 / 2 or more of the average particle diameter accounted for 5% or less of all 400 nickel nanoparticles. In other words, the proportion of particles that deviate significantly from the average particle diameter in the particle size distribution was low, and the particle size distribution was sharp, so it was confirmed that the nanoparticles had excellent thin film formability and filling properties into extremely narrow gaps.
[0077] In addition, as shown in Table 1, the nickel nanoparticles of the present invention had a CV value of 0.25 or less even when measured with a high-resolution SEM with a secondary electron resolution of 1.0 nm or less at an acceleration voltage of 15 kV. High-resolution SEM can adequately detect the presence of small nickel nanoparticles (hereinafter referred to as "small nickel nanoparticles") with a particle size of less than 20 nm, particularly less than 5 nm, and therefore more accurately reflects the actual state of the CV value. The nickel nanoparticles of the present invention have a smaller content of small nickel nanoparticles compared to nickel nanoparticles of the prior art, and therefore have a CV value of 0.25 or less even when measured with a high-resolution SEM.
[0078] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment.
Claims
1. Nickel nanoparticles having an average particle size of 5 to 100 nm, a nickel component contained in 100 parts by weight of a metal component of 99.5 parts by weight or more, and lithium of 0.00003 parts by weight to 0.5 parts by weight, Nickel nanoparticles, characterized in that, in a total of 400 nickel nanoparticles photographed with a scanning electron microscope having a secondary electron resolution of 1.0 nm or less at an accelerating voltage of 15 kV, the combined number of particles having a particle diameter of 1 / 2 or less and particles having a particle diameter of 3 / 2 or more, relative to the average particle diameter, accounts for 4.2% or less.
2. A method for producing nickel nanoparticles by heating a nickel complexing reaction solution obtained by reacting a nickel salt with a reducing agent to reduce nickel ions in the nickel complexing reaction solution, comprising: A method for producing nickel nanoparticles, comprising the steps of blowing in 0.1 to 5 L / min of nitrogen per 100 g of nickel complex reaction solution, adjusting the power of a stirrer to within a range of 0.025 to 0.1 kW, and then heating the solution to 190 to 240°C to produce nickel nanoparticles.
3. The method for producing nickel nanoparticles according to claim 2, wherein the nitrogen flow rate is changed in the temperature range of 190 to 215 ° C.
4. The method for producing nickel nanoparticles according to claim 3, wherein the nitrogen flow rate is adjusted to 2 to 4 L / min below 200 ° C. and 0.1 to 1.8 L / min above 200 ° C.
5. A paste material comprising the nickel nanoparticles according to claim 1 mixed with a resin.
6. A multilayer ceramic capacitor, comprising the nickel nanoparticles according to claim 1 as an electrode material.
Citation Information
Patent Citations
Method for producing nickel powder having hcp structure
JP2006249512A
Method for producing nickel particle and nickel complex suitably used therein
JP2010064983A
Metal particle production method and metal particle
JP2018109210A
Nickel powder and conductive paste
JP3280372B2
Method for producing nickel particles
WO2016052067A1